Ocorrência de fungos em amostras recebidas no laboratório de micologia e proteção de plantas da Universidade Federal de Uberlândia no período de 2001 a 2008 - Barros, Fernanda Carvalho (2010)
The present work reports the occurrence of fungi on crops of economic importance in the region of Uberlândia, Alto Paranaíba and some cities of Goiás, by the analysis of reports generated by Laboratório de Micologia e Proteção de Plantas (LAMIP), Universidade Federal de Uberlândia, on samples of seeds or plant parts, from the year 2001 to 2008. The reports analyzed were classified by crop and, subsequently, notes were taken on the pathogens that were reported, on the type of analysis performed and on the amount of reports analyzed per crop. Two thousand four hundred ninety eigtht reports on samples of cotton, brachiaria, coffee, bean, maize and soybean were analyzed. Thirty six genera of fungi were found, and Deuteromycetes was the main cause of diseases, counting 82% of all occurrences. The main causal agent was Fusarium sp., which was responsible for 956 occurrences (18%), followed by Cladosporium sp. (682 occurrences, 13%) and Cercospora sp. (502 occurrences, 9%). Among the crops studied, soybean presented the largest amount of reports, 2071 (82% of all reports), followed by maize (127 reports, 5%), and bean (125 reports, 5%). Among the methods performed in LAMIP, the seed sanity test is the most required, followed by visual analysis and, last, the isolation.